A Dialogue on Social Inquiry: Expanding Our Understanding of Sociological Thinking - Dhakal, Rebat Kumar (Social Inquiry: Journal of Social Science Research, 2019)
Highlights Social inquiry is much more than the study of society. It further excavates historical facts, critically reflects on everyday happenings, and envisions the future we wish to create. The intent of initiating this dialogue on social inquiry is two-fold: a) to offer a sociological perspective (i.e. ‘thinking sociologically’), and b) to expand our understanding of sociological thinking. Sociological thinking can be developed by examining the periphery of the core. Context matters in understanding any phenomenon under the sociological microscope. Sociological thinking allows many different viewpoints to coexist within a larger structure and that it respects pluralism. Sociological thinking is about developing or providing a perspective to examine social nuances. Sociological thinking should act as a means for social transformation. Social inquiry serves as a methodology for the social sciences and humanities. It deals with the philosophy of social science and the workings of the social world – giving a way for understanding both the biosphere and the sociosphere.